Design of Multi-Axis Servo Driver Based on FPGA - Zeng, Yu; Huang, Jiye; Gao, Mingyu (Recent Advances in Electrical & Electronic Engineering, 2017)
Background: Multi-axis servo driver based on FPGA is designed and implemented for the control of multiple alternating current (AC) servo motors in one numeric control (NC) system. Owing to the parallelism of field programmable gate array (FPGA), the highly integrated architecture not only reduces the spatial volume of the control system, but also improves the harmonious ability between different motors. Method: Moreover, the proposed predictive control method for each one axis not only improved the accuracy of position tracking and speed tracking, but also reduced the current fluctuation of the motor when its speed was changed. The methods implemented in this paper improved the response swiftness of NC systems. Conclusion: The measurements of current loop, speed loop and position loop on the three-axis machine can validate this algorithm.
Keywords: Multi-axis servo driver